Biodegradation of Cyclohexanol by Microorganisms Isolated From Oil Spilled Soil around Namakkal - Kartheek, B. R. (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT The hydrocarbon degrading organisms were isolated from the oil spilled area in and around Namakkal and identified bacterial and fungal species such as Pseudomonas, Bacillus, Micrococcus, Aspergillus, Rhizopus, Mucor and pencillium. The ability to degrade cyclohexanol in pure and mixed cultures was tested in the laboratory condition by using turbidometry growth curves and the degraded hydrocarbons using thin layer chromatography. Of all the isolates Pseudomonas sp. showed higher degrading ability (68.8%) than others (Bacillus sp.54.64%, Micrococcus sp. 44.1%) equaling to mixed cultures (81.1%) Key words: Oil degradation, Cyclohexanol, Bacteria, Oil spill